Recent development in black phosphorus nanomaterials for anticancer applications - Gao, Siyang; Wang, Yuelong; Sun, Jianwei; Zhang, Zhihui (Frontiers in Biomaterials Science, 2023)
Black phosphorus (BP), also referred to as phosphorene, has gained significant attention in recent years due to its unique structure and properties since its successful exfoliation in 2014. BP’s remarkable optical and mechanical properties, electrical conductivity, and electron transfer capabilities position it as a promising alternative to graphene for various biomedical applications. This article provides an overview of the use of BP in cancer imaging, drug delivery, and combination therapy, as well as the challenges and prospects of utilizing BP in practical biomedical applications. While BP shows great potential for biomedical applications, practical implementation remains challenging. Therefore, this review article aims to summarize the latest research on BP and provide insights into its future applications in the biomedical field.